Prajuru Desa’s Role in Mediating Inheritance Right Disputes for Men “Nyeburin” after Divorce in Tabanan Regency - Putu Sekarwangi Saraswati; Ida Bagus Gede Subawa; Kt. Sukawati Lanang P. Perbawa (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2022)
The purpose of this study was to analyze the role of traditional village prajuru in mediating inheritance rights disputes for men nyeburin after divorce in Tabanan Regency. The research method used is an empirical research method. Data collection techniques using document study techniques and interview techniques. The results showed that the role of the traditional village prajuru in mediating the inheritance rights dispute of men nyeburin after divorce in Tabanan Regency as one of the obligations of the adat prajuru as the party who has legal authority in the Adat Village in resolving customary problems, the initial stage is carried out case analysis which was followed by a joint meeting with the disputing parties, then related to inheritance rights as stated in awig-awig, in fact, was directed to conduct deliberations for consensus in a family manner by upholding the principle of kinship and the principle of parimatma as the main principle of inheritance distribution so as to obtain a fair and equitable agreement. does not cause problems between siblings.